Composition and Diversity of Natural Bacterial Communities in Mabisi, a Traditionally Fermented Milk - Moonga, Himoonga Bernard; Schoustra, Sijmen E.; van den Heuvel, Joost; Linnemann, Anita R.; Samad, Md Sainur; Shindano, John; Smid, Eddy J. (Frontiers in Microbiology, 2020)
Many traditionally fermented milk products such as mabisi involve spontaneous fermentation, which can result in bacterial community composition variation due to selection pressure. The aim of this study was to determine the composition of bacterial communities in the different types of mabisi produced across Zambia and identify the factors that influence their composition. Samples of mabisi were collected across the country, and analysed for pH and bacterial communities using 16S rRNA amplicon sequencing. We found that the bacterial community composition was dominated by members of two phyla, i.e., Firmicutes and Proteobacteria, from which the top 10 most abundant genera were Lactococcus, Lactobacillus, Streptococcus, Enterobacter, Citrobacter, Klebsiella, Kluyvera, Buttiauxella, Aeromonas and Acinetobacter. The most dominant genus was Lactococcus, which was present in all types of mabisi produced from all regions. The mabisi products from traditional mabisi production regions (TMPRs) were dominated by lactic acid bacteria (LAB) whereas products from non-TMPRs were dominated by non-LAB species. Tonga mabisi, the most popular type of mabisi produced in non-TMPRs, had the most complex and diverse bacterial community composition compared to the other types, which included barotse, backslopping, creamy and thick-tonga mabisi. Other factors that influenced bacterial community composition were type of fermentation container, type of producer, fermentation duration and pH. This study provides new insights that can be applied in starter culture development as well as microbial functionality studies.